Developing (super)citizenship: constituting idealized American citizenship in the Avengers: Earth's mightiest heroes - Luurs, Geoffrey, author; Anderson, Karrin, advisor; Diffrient, David Scott, committee member; Marx, Nicholas, committee member; Martey, Rosa, committee member (Colorado State University. Libraries, 2014)
This thesis explores two elements of character design in select episodes from the animated series The Avengers: Earth's Mightiest Heroes (Disney XD 2010-2012) that guide audiences towards dominant readings of idealized American citizenship utilizing both close textual analysis and ideographic criticism. I argue that select episodes of The Avengers: Earth's Mightiest Heroes contain representations of hyper-patriotic Americanized superheroes and un-American super villains which work together to teach viewers about dominant ideologies of Americanness and un-Americanness. In doing so, the text directs viewers towards a specific understanding of how to become idealized American (super)citizens.
Keywords: media studies; constitutive rhetoric; The Avengers; Captain America; citizenship